2020
DOI: 10.1101/2020.07.20.212019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep loss drives brain region- and cell type-specific alterations in ribosome-associated transcripts involved in synaptic plasticity and cellular timekeeping

Abstract: Sleep and sleep loss are thought to impact synaptic plasticity, and recent studies have shown that sleep and sleep deprivation (SD) differentially affect gene transcription and protein translation in the mammalian forebrain. However, much less is known regarding how sleep and SD affect these processes in different microcircuit elements within the hippocampus and neocortex - for example, in inhibitory vs. excitatory neurons. Here we use translating ribosome affinity purification (TRAP) and in situ hybridization… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 66 publications
8
7
1
Order By: Relevance
“…We first validated cell type-specific transcript enrichment from Camk2a+ and pS6+ cell populations, using qPCR. Consistent with recent data (36), relative to Input mRNA, Camk2a+ TRAP produced similar mRNA levels of Arc, Cfos, Homer1a, Glua1, and Vglut1 transcripts and reduced expression of interneuron and glial cell markers. In light of hemizygosity for HA-Rpl22, this is consistent with roughly twofold enrichment of excitatory markers relative to Input.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We first validated cell type-specific transcript enrichment from Camk2a+ and pS6+ cell populations, using qPCR. Consistent with recent data (36), relative to Input mRNA, Camk2a+ TRAP produced similar mRNA levels of Arc, Cfos, Homer1a, Glua1, and Vglut1 transcripts and reduced expression of interneuron and glial cell markers. In light of hemizygosity for HA-Rpl22, this is consistent with roughly twofold enrichment of excitatory markers relative to Input.…”
Section: Resultssupporting
confidence: 90%
“…2B and 4). Pathways affected by SD-across neuronal populations and across both subcellular compartments-were those linked to regulation of transcription, consistent with prior findings (4)(5)(6)36) and the AMPK, IL-3, IGF1, and PDGF signaling pathways. Critically, AMPK (70) and IGF1 signaling (71) have been implicated in homeostatic sleep responses-that is, changes in sleep architecture of brain oscillations-following SD.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is consistent with our recent work, showing that expression of the immediate early gene Arc is increased after SD in the somatosensory cortex while simultaneously being suppressed in hippocampal DG (19). More recently, we have found that while SD drives higher expression of a number of activity-regulated genes in both pyramidal cells and PV+ interneurons in the neocortex, expression of the same genes in the hippocampus is refractory to SD (63). Together, these findings might suggest that SD-driven activation of Sst+ interneurons, leading to general network inhibition, could be unique to the hippocampal network.…”
Section: Neurosciencesupporting
confidence: 93%